COMMUNITY EMPOWERMENT BASED ON UNDERWATER EDUCATIONAL TOURISM IN THE LHOK LAMTEUNGOH CUSTOMARY LAW MANAGEMENT AREA (WK-HAL) SYNERGISM WITH USK IN SUPPORTING PTNBH CAMPUS - Sayyid Afdhal El Rahimi; Ichsan Setiawan; Irwan; Thaib Rizwan; Chaliluddin; Ilham Zulfahmi; Muslim; Razali Thaib; Junaidi M. Affan (Jurnal Pengabdian Bangsa, 2024)
The Laot Lhok Lamteungoh traditional legal management area has marine natural characteristics consisting of shallow sea areas with coral reef ecosystems in several places, one of which is on Tuan Island, and several other points to the west-south in Peukan Bada District, Aceh Besar Regency. Coral reef areas are resources that must be conserved and provide income for the surrounding communities. PKMBP 2023 seeks an integrated program which will ultimately produce prospective entrepreneurs in the marine or maritime services sector, especially underwater tourism from traditional fishing communities. Service activities have been carried out for approximately 6 months June-November 2023 with socialization activities, FGDs, and a number of trainings and product placements in designated locations. The outputs produced in this activity include IPRs in the form of Copyright certificates, artificial reef prints, artificial reef products, mass media publications, and service journal publications. All targets were achieved as planned.